Building a Community Adaptive Capacity Model: A Case Study of the Tanjungmas Sub-District in Semarang Municipality - Intan Hapsari Surya Putri; Rukuh Setiadi (The Indonesian Journal of Planning and Development, 2020)
Climate change has pushed communities to make continued adjustments in various aspects of their life in order to adapt and survive. Adaptive capacity is a key concept in understanding this context. Although a number of researches in the discipline of social sciences have examined the meanings and categories of adaptation capacity, the extent to which this knowledge is used in the field of physical geography has not been adequately studied. Most studies on adaptive capacities within this discipline are focused largely on measuring the level or status of adaptation capacity (i.e. high, medium, or low) in a given region. Moreover, these studies have typically interpreted adaptation capacity as rigid and static. Thus, it sets the same index for all adaptive capacity categories. Sometimes it provides a varied index, but it does not give adequate consideration to the actual condition influencing adaptation capacity (i.e. the characteristic of adaptation goals, actors, resources, and etc.). With a case study approach focused in Tanjungmas Sub-district, this study aims to build a conceptual model which connects overall adaptive capacity categories using qualitative methods. We interviewed 18 key persons including sub-district officers, community leaders, women associations, and other local organisation members. This model may help researchers in the area of physical geography to conceptualize adaptation capacities and to establish an index that more accurately reflects local conditions following additional brief field assessments.